(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mukherjee is also a writer of non-fiction, which includes scholarlyarticles, essays and sociopolitical commentaries. Indeed it is impossible toread Mukherjee’s fiction without recognizing that it engages with and extendsmany of the central questions raised by her other prose works. Accumulatively,her writings attest to her ideological envisioning of herself as a pioneer ofnew territories, experiences and literatures. It can perhaps be said that like the migrant themes she explores in herwriting, Mukherjee’s biography itself, in terms of her multiple movementsacross national boundaries, testifies to what Timothy Brennan, referring to thenew literary aesthetic created by the forces of migration and movement, calls’a kind of perennial immigration’. Indeed, Mukherjee’s life, like her writings,can be read as a text that exemplifies a state of perpetual journeying from afixed and bounded narrative of home and belonging.